2007
DOI: 10.1007/s11816-007-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hemagglutinin-neuraminidase protein of Newcastle disease virus in transgenic tobacco

Abstract: Newcastle disease is one of the most important pathogens of domestic poultry including chickens. The hemagglutinin-neuraminidase (HN) of Newcastle disease virus is the principal target of neutralizing and protective antibodies against Newcastle disease. In this paper, we transformed tobacco plants with Agrobacterium tumefaciens EHA105 to generate the plants expressing HN of Newcastle disease virus (NDV). The insertion and copy numbers of HN gene in the genomic DNA of phosphinothricin-resistant plants were conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 48 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…The main candidates for developing a vaccine against the disease are fusion protein (F) and hemagglutiningneuraminidase protein (HN) since they are both exposed on the surface of the virus and take part in the infection. HN protein has been expressed in N. benthamiana Lai et al, 2013), potato (Berinstein et al, 2005) and tobacco (Hahn et al, 2007), F protein has been expressed in transgenic rice , potato (Berinstein et al, 2005) and maize (GuerreroAndale et al, 2006). These experiments proved that HN and F proteins can be successfully expressed in transgenic plants and that obtained proteins are immunogenic when delivered to either mice or chickens.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…The main candidates for developing a vaccine against the disease are fusion protein (F) and hemagglutiningneuraminidase protein (HN) since they are both exposed on the surface of the virus and take part in the infection. HN protein has been expressed in N. benthamiana Lai et al, 2013), potato (Berinstein et al, 2005) and tobacco (Hahn et al, 2007), F protein has been expressed in transgenic rice , potato (Berinstein et al, 2005) and maize (GuerreroAndale et al, 2006). These experiments proved that HN and F proteins can be successfully expressed in transgenic plants and that obtained proteins are immunogenic when delivered to either mice or chickens.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
“…These experiments proved that HN and F proteins can be successfully expressed in transgenic plants and that obtained proteins are immunogenic when delivered to either mice or chickens. Both maize-produced NDV F protein (Guerrero-Andrade et al, 2006) and tobacco-produced HN protein (Hahn et al, 2007) have been found to be immunogenic in orally immunized chickens; oral immunization with F protein gave 100 % protection of chickens against nasal challenge with NDV, while in the case of HN protein protection against nasal NDV challenge failed but the authors reported a big increase in anti-HN serum IgG levels 28 days after vaccination, increased by 2-fold in 40 % of examined chickens and 4-fold in 20 % of examined chickens (Hahn et al, 2007). HN and F proteins, co-expressed in potato, have been shown to elicit anti-NDV antibodies in intraperitoneally immunized mice and serum IgG at levels comparable to those elicited in mice fed with nontransformed plants soaked in NDV (Berinstein et al, 2005), while the intestinal fluids of those mice also showed considerable IgA and IgG levels.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Each system has its advantages and limitations and the method of choice is largely depending on what kind of fish vaccines are to be expressed, as briefly described in Table 2. To date, both food and non-food crops (especially tobacco plant) have been used for the development of a number of animal vaccines, such as a poultry vaccine against Newcastle disease (Hahn et al 2007; Yang et al 2007; Li et al 2007; Gómez et al2009; Van Eck and Keen 2009; Wu et al 2009: for reviews see Floss et al 2007 and He et al 2008), rabies (Ashraf et al 2005; Loza-Rubio et al 2008; Roy et al 2010; Loza-Rubio et al 2012), Porcine reproductive and respiratory syndrome virus (PRRSV) and Porcine post-weaning diarrhea in piglets (Chen and Liu 2011; Kolotilin et al 2012). The vaccine against Newcastle disease was the first plant-made animal vaccine receiving regulatory approval from the US Department of Agriculture (USDA) Center for Veterinary Biologics in 2006 (www.thepoultrysite.com/poultrynews/8949/usda-issues-license-for-plant-cell-producednewcastle-disease-vaccine-for-chickens; Joensuu et al 2008).…”
Section: Exploitation Of Plant Genetic Engineering For Low Cost Produmentioning
confidence: 99%
“…Plant expression systems have advantages over other in vitro expression systems in terms of low production costs (Giddings et al 2000;Ohya et al 2001;Daniell et al 2001;Leelavathi & Reddy 2003;Chen et al 2004;Arlen et al 2007;Hahn et al 2007). Although expression was lower than in other systems, the cost of producing recombinant proteins in plants could be 10 to 50-fold lower than producing the same protein by Escherichia coli fermentation, depending on the crop (Kusnadi et al 1997).…”
Section: Y Wu Et Almentioning
confidence: 99%